2020
DOI: 10.1097/dad.0000000000001658
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Sarcoma With Cutaneous Presentation in a 4-Year-Old Boy

Abstract: We report a case of a 4-year-old Brazilian boy, who presented with an erythematous and painful nodule involving the skin of his left arm. Immunohistochemistry was performed for S100, SOX10, CD34, desmin, SMA, HMB-45, CD1a, and CD163, and fluorescence in situ hybridization for EWSR1 gene rearrangement using a break-apart probe was completed. Immunohistochemistry showed bland spindle cells with “floret-like” appearance simulating a giant cell fibroblastoma; tumor cells were positive for S100 and SOX10; neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…They make up only 1% of all soft tissue sarcomas 3,4 . The prognosis is usually poor with some studies citing a 63% survival rate at 5 years and 36% at 10 years 5,6 . However, a large case series indicating follow‐up of 33 patients with CCSST indicates ten alive patients without evidence of disease, as in our case 6 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They make up only 1% of all soft tissue sarcomas 3,4 . The prognosis is usually poor with some studies citing a 63% survival rate at 5 years and 36% at 10 years 5,6 . However, a large case series indicating follow‐up of 33 patients with CCSST indicates ten alive patients without evidence of disease, as in our case 6 .…”
Section: Discussionmentioning
confidence: 66%
“…While rare, CCSST has been observed to have a significant myxoid component, which might be confused with other myxoid tumors such as cellular blue nevus, malignant blue nevus, malignant peripheral nerve sheath tumor, synovial sarcoma, neurothekeoma, myxofibrosarcoma, and myxoid malignant melanoma 2 . Lastly, CCSST can also occasionally present at atypical sites such as the head and neck 12 or in patients not within the expected age range 5 . The common factor for these atypical CCSST tumors, despite variances in clinical or histopathological presentation, is positive EWSR1/ATF1 fusion gene, highlighting the importance of fluorescence in situ hybridization if there is any suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…This localization is exceptionally rare, but it can pose significant diagnostic challenges as rare cases of intraepidermal involvement have been reported, and the tumor cells are positive for melanocytic markers such as S100, SOX10, HMB45, MelanA, or MiTF. In such instances, molecular analysis is mandatory in order to assess the rearrangement of the EWRS1 gene [ 61 , 62 ]. PRAME analysis should be considered in such cases as Kline et al demonstrated that it is significantly less expressed in PEComa and clear cell sarcoma than in melanoma [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, granular cell tumor expresses S-100 and SOX10 [ 8 ]; malignant melanoma expresses HMB45, Melan-A and S-100 [ 9 ]; alveolar rhabdomyosarcoma expresses Desmin and MyoD1 [ 10 ]; paraganglioma expresses Syn, S-100 and SOX10 [ 11 ]; PEComa expresses HMB-45, Melan-A, SMA, Desmin and Calponin [ 12 ]; clear cell sarcoma of soft tissue expresses S-100, SOX10, HMB-45 and Melan-A [ 13 ]; metastatic ccRCC expresses CK(p), EMA and CD10 [ 14 ]. Regarding this case, S-100, SOX10, Melan-A, S-100, Desmin, MyoD1, Syn, HMB45, Melan-A, CK (p) and CD10 were all negative while only Ki-67 and SMA was positive, based on which these common soft tissue tumors mentioned above were excluded.…”
Section: Discussionmentioning
confidence: 99%